2016
DOI: 10.1093/jhps/hnw021
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative lumbar plexus block provides superior post-operative analgesia when compared with fascia iliaca block or general anesthesia alone in hip arthroscopy

Abstract: The objective of this study is to retrospectively examine the effects of pre-operative fascia iliaca (FI) and lumbar plexus (LPB) nerve blocks on post-operative pain and secondary post-operative variables following arthroscopic surgery of the hip. Subjects undergoing arthroscopic surgery of the hip received one of three pre-operative anesthetic techniques; general anesthesia only, general anesthesia with FI or general anesthesia with LPB. Patient reported pain scores (0–10) were recorded at 0, 30, 60, 90 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…35 LPBs have also been used effectively for postoperative pain, but they require significant technical expertise and are associated with a significant complication risk. 27,34,36 Schroeder et al 27 performed a retrospective matched-cohort study in which they reviewed the records of patients who underwent hip arthroscopy and received an LPB preoperatively. The peak PACU pain scores were significantly improved in patients receiving an LPB.…”
Section: Discussionmentioning
confidence: 99%
“…35 LPBs have also been used effectively for postoperative pain, but they require significant technical expertise and are associated with a significant complication risk. 27,34,36 Schroeder et al 27 performed a retrospective matched-cohort study in which they reviewed the records of patients who underwent hip arthroscopy and received an LPB preoperatively. The peak PACU pain scores were significantly improved in patients receiving an LPB.…”
Section: Discussionmentioning
confidence: 99%
“…Rebound pain has also been reported in lower limb nerve blocks [14,15,19,73]. Femoral nerve blocks provide effective analgesia for knee surgeries with limitations being rebound pain and increased risks of falls due to quadriceps weakness [19,74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Wolff et al reported significantly lower pain scores up to 2 h post-operatively in patients undergoing arthroscopic hip surgery under lumbar plexus versus fascia iliaca block [73]. Regardless of pain scores, most of the patients received a standard dose of oxycodone as soon as they could tolerate oral medications.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a previous retrospective review, researchers from our group found lumbar plexus blockade to be superior to fascia iliaca blockade as well as general anesthesia alone. 25 However, lumbar plexus blockade continues to present several concerns, including but not limited to dependence on the experience and comfort level of the administering anesthesiologist, concomitant postoperative motor blockade, postoperative fall risk, and the risk of epidural or intravascular injection. As a result of these concerns, we continued to investigate alternative methods for obtaining optimal postoperative pain control after hip arthroscopy.…”
mentioning
confidence: 99%